2018
DOI: 10.31227/osf.io/3ub4t
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pengantar Manajemen

Abstract: CITATIONS 0 READS 26 2 authors: Some of the authors of this publication are also working on these related projects: ANALISIS SIKAP PENGGUNA JASA LAYANAN The user has requested enhancement of the downloaded file. KATA PENGANTARSegala puji bagi Allah, yang telah memberikan kenikmatan, hidayah, taufik dan inayah-Nya sehingga penulis dapat menyelesaikan penulisan buku ini. Sholawat beriring salam saya persembahkan kepada junjungan Nabi Besar Muhammad SAW, semoga kita mendapatkan syafaatnya di yaumil akhir. Aamiin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
0
5
0
6
Order By: Relevance
“…The development of e-commerce business in Indonesia continues to increase from year to year. Harahap and Amanah (2018) prove that current consumer behavior in Indonesia tends to prefer online shopping over offline shopping. This is supported by a graph of the development of e-commerce transactions in Indonesia during the period 2014-2018 as shown in figure 2 From Figure 2 above, it can be seen that the value of e-commerce transactions in Indonesia has positive trend that continues to increase during the period of 2014 to 2018.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The development of e-commerce business in Indonesia continues to increase from year to year. Harahap and Amanah (2018) prove that current consumer behavior in Indonesia tends to prefer online shopping over offline shopping. This is supported by a graph of the development of e-commerce transactions in Indonesia during the period 2014-2018 as shown in figure 2 From Figure 2 above, it can be seen that the value of e-commerce transactions in Indonesia has positive trend that continues to increase during the period of 2014 to 2018.…”
Section: Introductionmentioning
confidence: 93%
“…In addition, Tazkiyyaturrohmah (2018) shows that there is a change in the lifestyle of people who are more interested in e-commerce activities to be one of the factors causing an increase in electronic payment transactions. Harahap and Amanah (2018) in their research on online shopping behavior in Indonesia, showed that the existence of ebanking made online shops develop rapidly. Supporting the research, Fatonah, et al (2018) proves that the electronic payment system can provide various facilities in transactions, provide transparency in transactions making it easier to trace transactions, save time and transaction costs.…”
Section: Introductionmentioning
confidence: 99%
“…Salah satu hal yang mendukung kinerja yang baik adalah prestasi kerja. Prestasi kerja yang dihasilkan setiap karyawan akan berdampak positif bagi perusahaan, oleh karena itu dengan memberikan penghargaan memberikan motivasi kerja paling banyak/dominan dipergunakan setiap perusahaan (Harahap & Amanah, 2018). Menurut Mangkunegara (2009) prestasi kerja adalah hasil kerja secara kualitas dan kuantitas yang dicapai oleh seorang karyawan dalam melaksanakan tugasnya sesuai dengan tanggung jawab yang diberikan kepadanya.…”
Section: Literature Reviewunclassified
“…Proses perencanaan yaitu bagian dari daur kegiatan manajemen yang terutama berhubungan dengan pengambilan keputusan (decision making) untuk masa depan, baik jangka pendek maupun jangka panjang. (Harahap & Amanah, 2018) Penelitian ini dalam jangka panjang dapat digunakan sebagai dasar evaluasi dalam pembuatan kebijakan perencanaan obat untuk pasien BPJS Kesehatan Rawat Jalan di Instalasi Farmasi.…”
unclassified